Spine Oncology—Metastatic Spine Tumors. Issue 3 (21st February 2017) - Choi, David; Bilsky, Mark; Fehlings, Michael; Fisher, Charles; Gokaslan, Ziya
Abstract: Surgery for spinal metastases remains the mainstay treatment for pain, instability, and neurological deterioration due to tumor infiltration of the spine. However, several new therapies are emerging which may improve outcomes further, and in some cases even replace the need for surgery. We now have a better understanding of which factors influence survival and quality of life after surgery, and this underpins the development and application of new treatments, and assessment of outcome. Depending on genetic subtyping of tumors, novel immunotherapies and chemotherapies may be very effective in prolonging quality of life. New surgical techniques allow smaller, quicker, and safer operations with less blood loss, pain, and quicker recovery after surgery. Radiation treatments have also leapt forward with the greater accuracy and higher doses possible from intensity-modulated photon radiation, stereotactic body radiation treatment, proton beam therapy, or carbon ion treatment. Combined with more advanced materials for vertebral body stabilization, computer navigation systems, and robotics, more can be done at earlier or later stages of the spinal disease than was previously possible, resulting in more options and improved outcomes for patients.